PEMBERDAYAAN MASYARAKAT MELALUI DIVERSIFIKASI OLAHAN DAUN KELOR - Miftahul Hasanah; Evia Riska Fitriana; Novia Indriati; Siti Masruroh; Sulastri Sulastri; Cahyuni Novia (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Sumbercenteng Village is a village located in Kotaanyar Sub-district of Probolinggo Regency of East Java Province. The inhabitants are mostly farmers. Moringa is one of plants that are easily found in community homes. It owns a lot of nutrition inside, unfortunately the community do not optimize the use of Moringa itself. The goal to be achieved in community service activities is to increase the income of the community groups of PKK mothers through the processing of various processed moringa into bakpia, nugget, and noodles. The method is done by using lecture and demonstration method along with training materials, and delivered directly by performing a presentation related to the process of making bakpia, nugget, and noodles ranging from raw materials, how to use the tools of production, the process of mixing the materials, cooking until packaging. The results of the whole 100% of partners can make a variety of processed moringa and can do the packaging well.